Perlindungan Hukum Pidana Terhadap Doxing Menurut Undang-Undang Informasi Dan Transaksi Elektronik - Intan Saripa Uweng; Hadibah Zachra Wadjo; Judy Marria Saimima (PATTIMURA Law Study Review, 2023)
ABSTRACT: Doxing is a deliberate public announcement through Internet media concerning one's personal data information by another without the consent of the data owner himself, whose purpose is to embarrass, threaten, intimidate or punish the individual identified, but doxing deeds are often performed in the digital era today that makes people feel they no longer have privacy. And doxing or cyberattacks by doxer (perpetrator of doxing) or cyberattacks were performed for the sake of satisfaction or personal gain that could harm doxing's victims themselves. The purpose of the study is to discuss the elements of doxing's criminal actions according to the information laws and electronic transactions and how the legal protection of doxing victims was provided by the information laws and electronic transactions. This research is a normative juridical research conducted with legislation approach, conceptual approach and case approach. The crime caused by the ease of person in accessing the internet is called cybercrime, one of the evils included in cybercrime is doxing. Doxing or online deployment of information with cyberstalking and cyberbullying shapes where personal person's personal information is searched and shared, thus violating their privacy and leading to further harassment. Doxing has elements: everyone, against the law, attacking someone's honor, alleging something to know common, in electronic forms and or electronic documents, and is done in electronic systems. In Indonesia, this related doxing regulation has existed only has not been formulated specifically. In the case of doxing, the victim is protected by ITE law. Regulated in Article 26 and the culprit can be required by article 46 and 48 ITE law. In addition to those listed in ITE laws, there are also other instruments governing related to doxing crimes.